2018
DOI: 10.1002/ijc.31982
|View full text |Cite
|
Sign up to set email alerts
|

Newly developed anti‐S100A8/A9 monoclonal antibody efficiently prevents lung tropic cancer metastasis

Abstract: The metastatic dissemination of cancer cells to remote areas of the body is the most problematic aspect in cancer patients. Among cancers, melanomas are notoriously difficult to treat due to their significantly high metastatic potential even during early stages. Hence, the establishment of advanced therapeutic approaches to regulate metastasis is required to overcome the melanoma disease. An accumulating mass of evidence has indicated a critical role of extracellular S100A8/A9 in melanoma distant metastasis. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 25 publications
(35 reference statements)
0
24
0
Order By: Relevance
“…Binds extracellular S100A8/S100A9 heterodimer and therefore reduces metastasis Pre-clinical [236] 2H8 S100P Binds S100P and therefore reduces tumour growth and metastasis Pre-clinical [237] miRNA miR-187-3p S100A4 S100A4 silencing results in reduced metastasis and EMT in HCC Pre-clinical [238] miR-149-3p S100A4…”
Section: Inhibitor S100 Target Mechanism Of Action Current Status Refmentioning
confidence: 99%
See 1 more Smart Citation
“…Binds extracellular S100A8/S100A9 heterodimer and therefore reduces metastasis Pre-clinical [236] 2H8 S100P Binds S100P and therefore reduces tumour growth and metastasis Pre-clinical [237] miRNA miR-187-3p S100A4 S100A4 silencing results in reduced metastasis and EMT in HCC Pre-clinical [238] miR-149-3p S100A4…”
Section: Inhibitor S100 Target Mechanism Of Action Current Status Refmentioning
confidence: 99%
“…In terms of neutralising the DAMP molecules S100A8 and S100A9, monoclonal Ab45 was identified to be the most selective among ten anti-S100A8/S100A9 antibodies. In vitro, Ab45 could inhibit S100A8/S100A9-stimulated chemotaxis, and in vitro significantly reduced lung metastasis within a melanoma model [236]. The anti-S100P antibody 2H8 was introduced to inhibit S100P-induced proliferation of pancreatic cancer cells and blocked increased survival induced by S100P after gemcitabine treatment.…”
Section: Neutralising Antibodiesmentioning
confidence: 99%
“…For instance, melanoma cells from distant organs induce S100A8/A9 expression in the lung. Conversely, melanoma cells possessing several receptors that sense the S100A8/A9 ligand are attracted to an enriched S100A8/A9 lung environment [163]. Similarly, S100A8/A9 attracts cancer cells in the lung in prostate cancer murine models [164].…”
Section: Clp and Metastatic Cancers In The Lungmentioning
confidence: 99%
“…Kinoshita et al developed a neutralizing anti-S100A8/A9 antibody for blocking ''seed and soil'' cross-talk and found that it efficiently suppressed organ tropic metastasis. 119 Given that numerous DAMPs are released after surgery, the feasibility for the application of neutralizing antibodies is limited. Therefore, therapies targeting the downstream inflammatory signals are better options in the perioperative period.…”
Section: Anti-damps and Related Pyroptosis/ Inflammatory Signalingmentioning
confidence: 99%